Numerical investigation of the effect of temperature and volume fraction on the thermal properties of polystyrene silver nanoparticle (PS/AgNPs) composites - Mohammed, Imrana Habibat; Yabagi, Jibrin Alhaji; Akusu, Patrick Ovie; Babakatcha, Ndanusa; Ladan, Muhammad Bello; Dada, Micheal; Kimpa, Mohammed Isah (Universitas Sebelas Maret, 2024)
In this paper, the effect of temperature and volume fraction on the thermal properties of polystyrene silver nanoparticle (PS/AgNPs) composites is numerically investigated. This polymer nanocomposite consists of different quantities of silver (Ag) nanoparticles incorporated in a polystyrene (PS) matrix. The temperature dependence of the core-shell nanoparticles is investigated in the framework of Maxwell model and the Rule of Mixture model for random nanocomposite. By modeling the nanoparticles as being spherical, the effect of volume fraction and temperature on the core-shell nanoparticles is studied via both models for spherical core-shell nanoparticles. Simulations are successfully carried out using MATLAB programming to account for the effective thermal response which occurs at the wide interface between materials. The results show that the thermal conductivity of the matrix material can be enhanced by embedding high thermal conductivity nanoparticles, but the effectiveness of such a strategy diminishes as the effective thermal response between the nanoparticles and matrix material increases. Further simulations indicate that the enhancement of thermal conductivity can be affected by the alignment of nanoparticles with respect to the temperature gradient. The values obtained from the analytical Maxwell model compared to Rule of Mixture model are in close agreement with the experimental valuesfor a spherical nanocomposite. The Sufer 16 software is further used to show the 2-D contour of thermal conductivity variation over particle volume fraction and temperature of polystyrene silver nanoparticles (PS/AgNPs) composite. The polystyrene silver nanoparticles composite are expected to have adequate potential for a wide variety of applications particularly in microelectronic industries.